Diversity, productive and reproductive potential of the forest palms of Butia capitata (mart.) becc. of Uruguay - Rivas, M.; Barilani, A. (Agrociencia Uruguay, 2004)
Butia capitata is distributed across the Atlantic littoral from Santa Catarina in Brazil to the department of Rocha in Uruguay. In Rocha, B. capitata form ample forest of palms (palmares), which are distributed in two regions Castillos and San Luis. These plant communities are recognized for their biodiversity, scenic and cultural value, and the traditional uses of the fruit. The absence of regeneration and the aging process of the coetaneous individuals that form the actual palmers, places these plants communities at a serious risk of extinction. The strategies proposed for the conservation of the palmer are the establishment of protected areas and the development of productions that are compatible with their conservation. The objectives of this work are to estimate the diversity for the two sites of palmares, Castillos and San Luis, and to estimate the reproductive and productive potential of both palmares. One population of Castillos, and another from San Luis, were used in this study. The characteristics registered were number of fruits per infrutescence, epicarp color, weight and diameter of complete fruits, weight of endocarp with seeds and of mesocarp, relationship between weights of endocarp and complete fruits, number of locules and of healthy seeds, and 1000 seeds weight The reproductive and productive per individual and per hectarea were estimated. The results indicate that for the most of the character there is a high level of differentiation between the populations of Castillos and San Luis, that justifies the establishment of protected areas in each region of palmares. the diversity found within the populations is in agreement with the genetic structure of allogamous species. The reproductive and productive potential of the Castillos population, encourages conservation plans based on grazing management and the productive utilization of the butiá. The conservation of the San Luis population is compromised because of its lower reproductive potential.